Role of the Aceh government in managing foreign labour - Nasrianti Razaly; Muhibuddin Muhibuddin (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
The 1945 Constitution, Article 27 Paragraph stated that “every citizen has the right to work and a decent living for humanity "The Manpower and Population Mobility Service noted that the number of foreign workers in Indonesia as of May 2021 reached 92,058 people and on 10 June 2020 it found 29 Chinese foreign workers brought in by PT. MPG and PT. Tjianjin, whose work permit has expired. Then on August 8, 2020, 37 out of 39 Chinese foreign workers who will work in the PLTU 3 and 4 projects entered through Cut Nyak Dhien Airport, who only have a visit visa, without a work permit. The research method used in this study is library research and documentation. In the literature research, secondary data will be obtained, which will provide descriptions of how the laws and regulations governing the placement of foreign workers are practiced. Conclusions and suggestions that can be concluded, Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number 12 of 2013 concerning Procedures for the Use of Foreign Workers, and the Role of the Aceh Government in Supervision of Foreign Workers in companies in the Aceh Legal Territory are carried out in accordance with Law No. 11 of 2006 concerning the Government of Aceh. It is hoped that the government and the government of Aceh can improve supervision of foreign workers as stipulated in Qanun No. 7 of 2014 concerning employment, the duties and functions of the government of Aceh in Article 1 of Qanun No. 7 of 2014 concerning employment according to the duties and functions of the Labour Inspection Sector, so that foreign workers can be supervised and limited in the use of work visas in Indonesia because currently foreign workers  in Indonesia is very easy to get a job without any restrictions in accordance with the applicable laws and regulations so as not to harm local workers.